VIRULENCE FACTORS, INTRACELLULAR SURVIVABILITY AND MECHANISM OF EVASION FROM HOST IMMUNE RESPONSE BY BRUCELLA: AN OVERVIEW - A. Gopalakrishnan; U. Dimri; M. Saminathan; M.I. Yatoo; G. Bhuvana Priya; Devi Gopinath; V. Sujatha; Y. Ajith; A. Suthar; C. Lawrence; K. Dhama (Journal of Animal and Plant Sciences, 2016)
Brucellosis is an important zoonotic and contagious bacterial disease caused by Brucella spp. It is one of the most ancient diseases having a worldwide prevalence with significant human morbidity. It also causes devastating economic losses in livestock of developing countries due to reproductive failure (abortion and stillborn) and is a major hurdle in international trade. Brucella has the capability to induce chronic infection in animals due to lack of selective preventive measures and inefficient antimicrobial therapies, and difficulty in elimination. The virulence factors of Brucella are involved in intracellularsurvival and replication within mononuclear phagocytic cells, preferentially macrophages in the host.Furthermore, Brucella pathogen has developed a battery of mechanisms to evade and/or modulate both innate and adaptive immune responses in their host. Also, the stealthy nature of Brucella can make it able to evade from pattern recognition receptors of the innate immune arm, which can lead to its escape from intracellular destruction and to eventually replicate within phagocytic cells. All these comprehension of Brucella can inhabit inside the phagocytes of infected host to promote their survival, persistence and multiplication. Therefore, the analysis of the interaction between pathogen and immune response is relatively new area of intense research. In this review, we discussed the pathogenesis of Brucella spp. mechanisms that permit intracellular survival, subvert autophagy process and evasion to host immune responses.
Keywords: Adaptive immunity; Autophagy; Brucella spp; Innate immunity; Intracellular survival; Mechanism of evasion from host; Virulence factors